Waste Cooking Oil Conversion To Biodeisel Catalized By Egg Shell Of Purebred Chiken With Ethanol As A Solvent - Hellna Tehubijuluw; I Wayan Sutapa; Mealan Lethulur (EKSAKTA: Journal of Sciences and Data Analysis, 2014)
The synthesis of biodiesel from the waste cooking oil was carried out using the catalyst from egg shell of purebred chiken with ethanol as a solvent. Synthesis of biodiesel was prepared in two steps, esterification and transesterification. Esterification was conducted in mol ratio of ethanol and waste cooking oil of  9:1 with H2SO4 as a catalyst. Mol ratio of ethanol and used cooking oil in the transesterification of  12:1 with the CaO catalyst of shell eggs. CaO catalyst was yielded by calcinations egg shell of purebred chicken on 1000 for two hours. Calcination product was characterized with XRD to determine of CaO. Result of biodiesel was characterized based on FTIR, H-NMR, dan ASTM (American Standard Testing of Materials). Theoretically,yielded of biodiesel was 58% and experiment was 36.779%.